Enabling Others to Win in a Complex World: Security Force Assistance and the Future of the Regionally Aligned Forces Mission in the Brigade Combat Team. - Walsh, Liam P. (Tufts Archival Research Center, 2015)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: As the U.S. Army looks to work in conflict prevention, the 2013 decision to align its major combat forces with a Geographic Combatant Command in the Regionally Aligned Forces concept serves as a groundbreaking new way to employ conventional Army forces. However, a case study of the U.S. Army's efforts at security force assistance during Operation Iraqi Freedom prove that there are multiple shortcomings in the organization and manning of Army forces to conduct security force assistance. This Capstone examines the security force assistance lessons from Iraq, and then provides recommendations as to how the Army could best optimize its core units to conduct effective and efficient security force assistance.